Nonlinear finite element analysis of simply supported composite beams stiffened with steel channel - Khalaf, Alyaa H.; Abbas, Abdalnassre M. (Basrah Journal for Engineering Sciences, 2016)
A composite beam is an accumulation of different materials so as to form a single unit to exploit the prominent quality of these materials according to their position within the cross-section of the composite beam. The present study investigates the structural behavior of six simply supported composite beams, in which a reinforced concrete T-beam is connected together with a steel channel located at the bottom of a T-beam by means of headed stud shear connectors. The used degrees of shear connection are (100%, 75%, 50%, and 38%). Three dimensional nonlinear finite element analysis has been used to conduct the numerical investigation for the general behavior of beams which are subjected to central point load. ANSYS 12.1 program code was used to estimate the ultimate loads, deflections, stresses, strains, end slip. Concrete was modeled by brick element (SOLID65), while the steel channel was modeled as brick element (SOLID45). Two-node discrete elements (LINK8) are used to represent the steel reinforcement and shear connectors. Perfect bond between the reinforcing rebars and the concrete was assumed. The load on beams was applied monotonically in increments up to failure. The reduction of the degree of shear connection from 100% to 38% causes increasing of strain, mid span deflection and end slip with an average of 3.95%, 13%, and 111% respectively, while the ultimate load decreases with an average of 7.3%. In order to observe the efficiency of the 3-D model, a comparison was made with available experimental work. Good agreement was obtained throughout this work between the finite element and available test results.